Thomas Moore’s creative works in the Russian literary critical reception of the 1820s the first half of the 1830s - N. Zhatkin, Dmitry (2019)
Objectives: The article is devoted to the study of literary-critical responses about Thomas Moore and his works published in Russian periodicals of the 1820s – the first half of the 1830s. Methods: The article is based on methodologically significant works of such leading Russian literary scholars as M.P.Alekseev, Alexander N.Veselovsky, V.M.Zhirmunsky, Yu.D.Levin, Yu.M.Lotman, B.V.Tomashevsky, V.N.Toporov, E.G.Etkind, as well as works on comparativistics science, theory and history of literary translation, intercultural communication. Cultural and historical, comparative research methods are used, as well as methods of integrated analysis. Findings: The first mentions about Thomas Moore in Russia began to appear in translated articles and brief notifications about the release of new books in the early 1820s. Many articles contained critical remarks about the work of the Irish bard, responses to his most significant works for the Russian public, among which are the poetic cycle «Irish Melodies», the oriental tale «Lalla Rookh» and the novel «The Epicurean». An Interest to Thomas Moore was maintained thanks to his work on the biography of Lord Byron, which caused many disapproving remarks from Russian literary criticism due to the circumstances accompanying its appearance. Novelty: Despite the appearance in the Russian press in the 1820s – the first half of the 1830. critical reviews about the work of Thomas Moore, he was traditionally perceived as one of the key figures of English romanticism, who was a part of the famous triumvirate of romantics along with Byron and Walter Scott. Moore turned out to be significant for Russian literature as a singer of Irish freedoms, an interpreter of Oriental motifs, a biographer and a like-minded person of Byron.